EFEKTIVITAS PELATIHAN SENAM KAKI ALAT PIJAT KAYU APIYU (SENAYU) TERHADAP SENSITIVITAS KAKI PASIEN DIABETES MELLITUS TIPE II. - Eva " Agustina; Yesi " Hasneli; Riri " Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this research was to determine the effectiveness of foot gymnastics APIYU (Senayu) before and after among patients with type II Diabetes Mellitus. The design of this research was “quasy experimental” designed by “Non-equivalent control group”. The total sample were 34 respondents whom fit the inclusion criteria and chosen by purposive sampling, which was divided into 17 respondents experimental group and 17 respondents control group. Measuring instruments used in both groups were monofilament and APIYU. In the experimental group was given the foot gymnastic APIYU (senayu) for 3 days before and after doing SENAYU and then the foot of respondents measured with monofilament. The analysis used univariate analysis to observe the respondents characteristics frequency and bivariate analysis by using Wilcoxon and Mann Whitney. The result of pre-post test showed a increasefoot sensitivity at 2,3 point of the right foot and increase at 2,0 point of the left footon the experimental group. The result of statistical test indicated a significant increase on the experiment group with p value 0,000 (p<0,05). In conclusion, foot gymnastics by using APIYU can increase the sensitivity of the foot in patients with diabetes mellitus type II.The results of this study was expected to be one of the nursing interventions to improve the sensitivity of the foot in patients with diabetes mellitus type II and this study was expected to minimize complications of patients foot with diabetes mellitus type II.Keywords: Diabetes mellitus, gymnastics foot APIYU (Senayu), sensitivity foot